72.6k views
9 votes
Answer for both boxes please :)​

Answer for both boxes please :)​-example-1

1 Answer

10 votes

Answer:

(0, - 3 )

Explanation:

Given the 2 equations

6x - 4y = 12 → (1)

- 6x + y = - 3 → (2)

Add (1) and (2) term by term to eliminate x, that is

0 - 3y = 9

- 3y = 9 ( divide both sides by - 3 )

y = - 3

Substitute y = - 3 into either of the 2 equations and solve for y

Substituting into (1)

6x - 4(- 3) = 12

6x + 12 = 12 ( subtract 12 from both sides )

6x = 0 , thus

x = 0

solution is (0, - 3 )

User Sungjoon
by
5.6k points